Pemanfaatan Teknologi Pembangkit Listrik Tenaga Pikohidro di Desa Pesucen Kabupaten Banyuwangi - Khairul Muzaka; Galang Sandy Prayogo; Dian Ridlo Pamuji (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The use of alternative energy is being promoted to replace the dependence on fossil energy such as coal. Coal is mostly used as fuel in power plants. The proven reserves of coal are 31.35 billion tons, if it is assumed that there are no discoveries of new reserves, the coal will last in 72 years. Therefore, the government through the National Energy Policy No. 79 of 2014 mandates the use of renewable energy at least 23% in 2025 and 31% in 2050. One of the energy sources that is often used as a substitute for fossil energy is water. The energy possessed by water can be used as electricity generation of Hydro Power Plant. Many villages in Indonesia have rivers and irrigation channels that have not been utilized as a new and renewable energy source, especially for micro and pico-scale power plants. One of the irrigations flows that have not been utilized is in the village of Pesucen, Banyuwangi Regency, East Java. The flow of the irrigation canal has a fairly heavy flow so it is suitable for a Pico Hydro Power Plant. The Pico Hydro Power Plant which will be made is expected to provide an alternative to generating electricity by utilizing existing irrigation channels which is located behind houses. In addition, the Pico Hydro Power Plant can reduce the dependence of residents on existing electricity sources and irrigation channels have more value than before